PENGUATAN EKONOMI DESA MELALUI PENERAPAN KONSEP EKONOMI SYARIAH DI DESA KAYU BESI, KECAMATAN PUDING BESAR, KABUPATEN BANGKA - Zikri Rahmani; Devi Valeriani; Eka Fitriyanti; Ayu Wulandari; M Afdal S; Agung Rizky Putra (Jurnal Abdi Insani, 2023)
Strengthening the village economy through the application of the sharia economic concept is an effort to make the village economy strong, large, modern and competitive based on Islamic law. The Community Service Program (PMTJ) at the Department level aims to increase the knowledge and understanding of the people in Kayu Besi village to apply Islamic economic concepts and values ​​in their daily economic activities. This community service activity at the department level (PMTJ) uses two stages, namely the preparation and implementation stages of the activity. The stages of implementing the activity consist of lectures, brainstorming and end with a question and answering discussion. The results of community service activities are providing education and understanding of the application of Islamic economic concepts such as; Sharia-based village cooperative financial system, knowing various examples of Riba transactions, the concept of Muzaroah (cooperation in agriculture), and so on. The conclusion of this service activity is to increase the knowledge of the Ironwood Village Community about the application of Islamic economic concepts in their daily economic activities.